Nurturing Roses and Urban Dreams by Utilizing Village Budgets for Sustainable Growth in Karangpring and Jubung - Siska Aprilia Oktaviani; Berlina Yudha Pratiwi; Fitriya Andriyani; Oryza Ardhiarisca (Universitas Pamulang, 2025)
This study aims to analyze the allocation of village funds for sustainable development and calculate the carbon footprint associated with village activities. Using a qualitative case study approach, data were collected through in-depth interviews with village heads and analysis of the 2023 Village Budget (APBDes) documents. The findings show that both villages allocate a significant portion of their budgets to infrastructure, community services, and social security. However, not all budget allocations directly contribute to measurable carbon emissions, only certain items such as raw materials, IT tools, and vehicles. This study contributes to the understanding of how effective budget allocation and sustainable practices can reduce carbon footprints and promote the importance of implementing sustainable development at the village level. Both villages in the study can significantly improve sustainable development efforts by focusing on providing environmentally friendly materials, improving energy efficiency, and involving community participation in planning. These findings can be a model for other villages in Indonesia that want to achieve sustainable development.